Salvage radiotherapy after high intensity focused ultrasound for prostate cancer - Dickinson, Peter (BMJ Case Rep, 2012)
High-intensity focused ultrasound (HIFU) is a technique that has been used to treat localised prostate cancer. There is no standard treatment for patients who relapse with prostate cancer following primary treatment with HIFU; here we report the case of a patient who was successfully treated with external beam radiotherapy for disease relapse following HIFU. To date, our patient remains disease free with no toxicity from his treatment.